2017
DOI: 10.22159/ajpcr.2017.v10i11.18156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alendronate on the Healing Time of Distal Radial Fractures Treated Conservatively: An Observational Study

Abstract: Objective: Although fragility fractures of the distal radius are common, osteoporosis treatment requires exploration as attempts to improve postfracture investigations have been only partially successful. Bisphosphonates may help minimize the risk of secondary fractures but being a potent antiresorptive agent; it raises concerns about adverse effects on the healing process. This observational study examines the effect of bisphosphonate (alendronate) on healing of acute fractures of distal radius through 66 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Osteoporosis status unknown – The randomized controlled trial by Duckworth et al [77] found no effect of bisphosphonates on union rate in the healing of a distal radius fracture. Also a retrospective study in patients with a distal radius showed no effect of bisphosphonate on the occurrence of radiological or clinical delayed union [86] .…”
Section: Resultsmentioning
confidence: 98%
“…Osteoporosis status unknown – The randomized controlled trial by Duckworth et al [77] found no effect of bisphosphonates on union rate in the healing of a distal radius fracture. Also a retrospective study in patients with a distal radius showed no effect of bisphosphonate on the occurrence of radiological or clinical delayed union [86] .…”
Section: Resultsmentioning
confidence: 98%